Vilcashuaman and its development as a cultural tourist destination in Ayacucho - Elescano Galarza, Javier (2022)
The province of Vilcashuamán, which in Quechua means “Sacred Falcon”, located in Ayacucho, presents great possibilities of consolidating a cultural tourist destination due to the ancestral heritage it has, since the times of the Chanca Confederation and later as part of the Inca Empire, and provide, at present, a possibility of integrating a cultural tourist circuit that stands out in the central area, with a tourist product that promotes sustainable development in the region. The present work presents as a proposal a program of activities to disseminate and develop this Tourist Destination according to the guidelines of PENTUR and the Regional Tourism Plan of Ayacucho 2013-2021, proposing actions that involve society, highlighting its cultural identity, respect for environment that promotes sustainable tourism development. Likewise, consolidate itself as a destination that reactivates internal tourism, post-pandemic.